2018
DOI: 10.1111/jog.13698
|View full text |Cite
|
Sign up to set email alerts
|

Daily walking is effective for the management of pregnant women with gestational diabetes mellitus

Abstract: AimThis study evaluated the usefulness of daily walking for gestational diabetes mellitus (GDM) management by analyzing the relationship between daily walking and glucose tolerance in pregnant women with GDM who were in the second trimester.MethodsThis longitudinal study was conducted at TOYOTA Memorial Hospital in Toyota, Japan, from January 2015 to June 2016. Pregnant women with GDM wore accelerometers on the waist for 7–12 weeks.ResultsSeventy‐three women with GDM were included in the present study; data co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 27 publications
(42 reference statements)
3
28
0
Order By: Relevance
“…Similar to medical nutrition therapy, Sklempe Kokic et al (Sklempe Kokic et al, 2018) reported that physical activity is a key component in initial GDM management. Physical activity improves insulin sensitivity and reduces fasting and postprandial glucose concentrations in patients with GDM (Hayashi et al, 2018). This study underlines that exercise interventions performed early in pregnancy can reduce the risk of excessive Gestational Weight Gain (GWG) in the first and early second trimester and can possibly reduce the incidence of GDM (Elvebakk et al, 2018); (Wang et al, 2015b).…”
Section: Management Of Gdmmentioning
confidence: 82%
“…Similar to medical nutrition therapy, Sklempe Kokic et al (Sklempe Kokic et al, 2018) reported that physical activity is a key component in initial GDM management. Physical activity improves insulin sensitivity and reduces fasting and postprandial glucose concentrations in patients with GDM (Hayashi et al, 2018). This study underlines that exercise interventions performed early in pregnancy can reduce the risk of excessive Gestational Weight Gain (GWG) in the first and early second trimester and can possibly reduce the incidence of GDM (Elvebakk et al, 2018); (Wang et al, 2015b).…”
Section: Management Of Gdmmentioning
confidence: 82%
“…Evidence from a cohort study of over 900 women with GDM found that moderate-intensity physical activity, as self-reported on the Pregnancy Physical Activity Questionnaire, was significantly associated with optimal glycemic control, defined as ≥ 80 % of self-monitored capillary glucose values meeting clinical targets [ 30 ]. In a small study of 24 women with GDM, there was an inverse association between daily steps (objectively assessed by device) and random blood glucose [ 31 ]. The authors also reported significantly lower random blood glucose among those who completed ≥ 6000 steps per day [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a small study of 24 women with GDM, there was an inverse association between daily steps (objectively assessed by device) and random blood glucose [ 31 ]. The authors also reported significantly lower random blood glucose among those who completed ≥ 6000 steps per day [ 31 ]. Another small study of 30 women with GDM showed significant improvement in fasting and postprandial glucose levels and lower insulin requirements following participation in low-intensity walking sessions [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent findings showed that physical activity during pregnancy could reduce the risk of GDM [6] . The study of Hayashi et al [7] suggested that walking could significantly reduce the level of random blood glucose for pregnant women with GDM. It was also recommend at least 6000 steps per day.…”
Section: The Risk Of Gdm Was Significantly Reduced By Physical Activitymentioning
confidence: 99%